The art of drawing people - Foster, Walter T. (Walter Thomas), 1891-1981; Powell, William F. (Artist); Yaun, Debra K.; Cardaci, Diane (Walter Foster, 2019)
Demonstrates how to create realistic portraits and figure drawings. Presents information on anatomy, variations by ethnicity and age, and drawing different poses.